2004
DOI: 10.1111/j.1365-2966.2004.08155.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances of planetary nebulae from optical recombination lines - I. Observations and plasma diagnostics

Abstract: We have obtained deep optical spectra of medium resolution for a sample of 12 Galactic planetary nebulae (PNe). Optical recombination lines (ORLs) from carbon, nitrogen and oxygen have been detected in 11 of them and neon ORLs in nine of them. All spectra were obtained by scanning a long slit across the nebular surface, yielding relative line intensities for the entire nebula that are suitable for comparison with integrated line fluxes measured in other wavelength regions using space‐borne facilities, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
81
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 44 publications
(65 reference statements)
15
81
0
1
Order By: Relevance
“…It can be seen that the electron temperature is roughly constant as a function of ionization potential. The electron temperature has also been determined from the Balmer jump to be 9300 K. (Liu et al 2004b). Some PNe show a gradient of electron temperature but if any gradient exists in this nebula, is can only be seen in the slightly higher temperatures for the lowest ionization potentials (presumably formed in the outer regions of the nebula).…”
Section: Electron Temperaturementioning
confidence: 99%
“…It can be seen that the electron temperature is roughly constant as a function of ionization potential. The electron temperature has also been determined from the Balmer jump to be 9300 K. (Liu et al 2004b). Some PNe show a gradient of electron temperature but if any gradient exists in this nebula, is can only be seen in the slightly higher temperatures for the lowest ionization potentials (presumably formed in the outer regions of the nebula).…”
Section: Electron Temperaturementioning
confidence: 99%
“…We also used two radio continuum flux densities at 4850 and 1400 MHz of 360 and 440 mJy respectively, which are averages of the data collected by Vollmer et al (2010). For the angular diameter we used 76 (Liu et al 2004). We adopted a distance of 740 pc (O'Dell et al 2009).…”
Section: Appendix B: Photometrymentioning
confidence: 99%
“…The method was slightly modified in that we used H-Ni model atmospheres from Rauch (2003). As input we used the UV and optical spectrum listed in Liu et al (2004). We rejected the SWS spectrum as it turned out that the aperture was mainly pointed at the central "cavity" and was therefore strongly biased towards the high excitation region of the nebula.…”
Section: Appendix B: Photometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the low cosmic abundances of n-capture elements (Asplund et al 2009), deep ultraviolet (Sterling et al 2002;Sterling & Dinerstein 2003;Williams et al 2008), optical (e.g., Hyung et al 2001;Sharpee et al 2003;Liu et al 2004;Zhang et al 2005;Sharpee et al 2007;Sterling et al 2009;Otsuka et al 2010Otsuka et al , 2011 and near-infrared spectroscopy (Likkel et al 2006;Sterling et al 2007;Sterling & Dinerstein 2008) of several Galactic and Local Group PNe revealed spectral features of these species. Abundances of these elements have now been estimated in approximately 100 PNe, allowing for an analysis of s-process elemental enrichments in a statistically meaningful sample of objects.…”
Section: Introductionmentioning
confidence: 99%